Peran Environmental Management Accounting (EMA) dalam Meningkatkan Efisiensi Lingkungan dan Kinerja Keuangan: Kajian Literatur Sistematis - Nurmalia Malahusna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to systematically examine the contribution of Environmental Management Accounting (EMA) in improving environmental efficiency and corporate financial performance. EMA is a modern accounting approach that integrates environmental considerations into managerial information systems to support more sustainable decision-making. The study applies the Systematic Literature Review (SLR) method using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, which consists of four main stages: identification, screening, eligibility, and inclusion. Literature searches were conducted across academic databases including Scopus, ScienceDirect, and Google Scholar, covering publications from 2014 to 2024. Out of 127 initially identified articles, 12 were selected based on strict inclusion criteria and topic relevance. The review reveals that EMA implementation significantly enhances environmental efficiency through improved waste management, energy optimization, and emission reduction. Furthermore, EMA contributes positively to financial performance via operational cost savings, regulatory compliance, and enhanced corporate reputation. Challenges identified include lack of system integration, limited managerial awareness, and insufficient environmental data. This research offers both theoretical and practical insights into strengthening sustainable accounting practices and supports the achievement of the Sustainable Development Goals (SDGs).